TARI NITI NAIK MAHLIGAI DALAM KARYA SENI LUKIS - Ari Alsia; Abd. Hafiz (Universitas Negeri Padang, 2021)
The purpose of the creation of this work is to visualize the procession of the Niti Naik Mahigai dance in a realist painting. The method of creating works uses five stages, namely preparation, elaboration, synthesis, concept realization, and completion. In the attainment of form through a combination of color, lines, form, and balance so as to produce interesting paintings. In the paintings that the author creates, tells the procession or stages of the Niti Naik Mahligai dance, totaling 10 works with titles; 1) Digendun, 2) Lah Jadi, 3) Niti Gunong Kaco, 4) Niti Telo, 5) Niti Gunong Paku, 6) Niti Gunong Buluh, 7) Niti Laun, 8) Niti Gunong Sword, 9) Ditumbak, and 10) Niti Laut Api.Keywords: Procession, Niti Naik Mahligai Dance, Painting.